The Role of VR in Education: A Two-Phase Review of Umbrella Reviews and Recent Primary Studies - Jeri Varjosalo; Paavo Raty; Ville Heilala; Raija Hamalainen; Tommi Karkkainen (IEEE Access)
The use of virtual reality (VR) in research and development has increased dramatically across various fields over the past decade, and education is no exception. To study the status and recent trends of VR research in learning, we present a novel two-phase systematic review: First, in a meta-umbrella review, we drew together the general essence of VR studies by summarizing 11 umbrella reviews in the field from 2017 to present. Second, we assessed more recent research trends by constructing a topic model of over 6530 primary studies published in 2023–2024. We found that VR has become increasingly popular, offering various benefits across different fields, including healthcare and education. In specific learning domains, VR has been used for chemistry and engineering laboratory training, gamified experiences, aviation training, and various school subjects such as history. VR in education was typically characterized by personalized immersive experiences that could adapt to the learner. However, the definitions of VR, especially concerning the amount of immersion, were varied. VR can motivate, control the environment, and help with difficult concepts. Long-term evidence of the effectiveness of VR training was still scarce. Learning standards or frameworks for the use and design of VR in education have not yet been used or formed and important aspects like immersion have not been fully utilized. The results indicate that, more thorough research with long-term data, standards, and clear operationalization of VR features are needed to truly establish the benefits and improvements VR can provide within the field of education and beyond.